Enhancing healthcare data security: a two-step authentication scheme with cloud technology and blockchain - Ussatova, Olga; Makilenov, Shakirt; Mukaddas, Arshidinova; Amanzholova, Saule; Begimbayeva, Yenlik; Ussatov, Nikita (Eastern-European journal of enterprise technologies, 2023)
In the modern world, medical data leakage has many external and internal threats. Information systems of medical organizations are constantly subject to various types of cyber-attacks and unauthorized penetration attempts, which leads to the publication of patient medical data online. Existing authentication schemes using blockchain technologies in medical organization systems ensure the integrity of medical data and secure access to patient data. However, one of the serious reasons for unauthorized access to the healthcare system is the human factor, which manifests itself in a negligent attitude towards account security, non-compliance with the rules and policies of information security, and transferring to third parties personal login details to the information system of a medical organization. This paper proposes a solution to this problem through an improved two-step authentication scheme using cloud technology and blockchain. The combined use of cloud technologies and blockchain is a distinctive feature of the proposed authentication scheme since it provides two levels of protection: 1) two-step authentication, the second stage of which includes biometrics through a mobile application. It prevents unauthorized access to the system by third parties; 2) cloud encryption keys for decrypting medical data, which are also accessed through the user's biometrics. The practical part of the paper includes the implementation of biometric login in Python using the OpenCV library. As a result of the practical part, unique fingerprint samples were obtained. The biometric user verification algorithm is designed for a mobile application, which we plan to implement in the future У сучасному світі витік медичних даних має багато зовнішніх і внутрішніх загроз. Інформаційні системи медичних організацій постійно зазнають різного роду кібератак і спроб несанкціонованого проникнення, що призводить до публікації медичних даних пацієнтів в мережі. Існуючі схеми автентифікації з використанням технологій блокчейн в системах медичних організацій забезпечують цілісність медичних даних і безпечний доступ до даних пацієнтів. Однак однією з серйозних причин несанкціонованого доступу до системи охорони здоров’я є людський фактор, який проявляється у недбалому ставленні до безпеки облікових записів, недотриманні правил і політик інформаційної безпеки, передачі третім особам особистих даних для входу в інформаційну систему медичної організації. У цій статті пропонується вирішення цієї проблеми за допомогою вдосконаленої двоетапної схеми автентифікації з використанням хмарних технологій і блокчейну. Відмінною рисою запропонованої схеми аутентифікації є поєднання хмарних технологій і блокчейну, оскільки вона забезпечує два рівні захисту: 1) двоетапна аутентифікація, другий етап якої включає біометрію через мобільний додаток. Запобігає несанкціонованому доступу до системи сторонніх осіб; 2) хмарні ключі шифрування для розшифровки медичних даних, доступ до яких також здійснюється через біометричні дані користувача. Практична частина статті включає реалізацію біометричного входу в Python за допомогою бібліотеки OpenCV. За результатами практичної частини отримано унікальні зразки відбитків пальців. Алгоритм біометричної верифікації користувача розроблений для мобільного додатку, який планується реалізувати в майбутньому